A Case Report of Early Therapeutic Intervention for Limb Girdle Muscular Dystrophy in Late Adolescence - Bajpai, Aakanksha (New Frontiers in Medicine and Medical Research Vol. 3, 2021)
This study describes the advantages of a strength and endurance training-based program in the early rehabilitation of patient with Limb Girdle Muscular Dystrophy (LGMD). Limb-Girdle Muscular Dystrophy-Type 2A (LGMD-2A) is an autosomal recessive disorder triggered by a mutation in the Calpain-3 gene (CAPN3) contributing to partial or complete protein deficiency. LGMD-2A is the most prevalent form of the disease in India, accounting for 47% of cases in the heterogeneous group. Here, we record a 22-year-old female with trouble walking due to proximal muscle weakness since one year and an elevated Creatine Phosphokinase (CPK) with abnormal muscle biopsy finding. The patient was granted an 8-week intervention & a prognosis was established.